Penerapan Algoritma A* untuk Pencarian Rute Terpendek pada Aplikasi Game Shoot'em Up - Hasniati; Syaiful Rahman; Suyono (AGENTS: Journal of Artificial Intelligence and Data Science, 2023)
The purpose of this research is to implement A* algorithm for finding shortest path in a shooter game. To design the system, use case diagram will be used to explain the functional requirements of the system, and the activity diagram to describe the system workflow. While in the application development that can be used in a desktop with a Windows operating system, Unity will be used. The testing methods used in this study are the black box method to validate that the game can run as designed, beta testing and software quality testing to verify that the A* algorithm was implemented well. The results of this study are 1) According to the results of black box testing, it can be concluded that all the buttons and features on the application manage to work as designed; 2) According to the result of endurance testing that have been done, it can be concluded that A* is very accurate and can find the shortest path in a short time, and the time used for the pathfinding is very dependant on the node count.